2018
DOI: 10.1016/j.jaridenv.2018.01.006
|View full text |Cite
|
Sign up to set email alerts
|

An ecohydrological stream type classification of intermittent and ephemeral streams in the southwestern United States

Abstract: An ecohydrological stream type classification was developed to improve decision making for ephemeral and intermittent streams at four military reservations in the southwestern U.S.: Fort Irwin, Yuma Proving Ground (YPG), Fort Huachuca, and Fort Bliss. Agglomerative hierarchical cluster analysis was used to classify stream reaches by ecohydrologic properties (vegetation, hydrologic, and geomorphic attributes derived using geographic information system analyses), and Classification and Regression Trees (CART) we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
35
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(45 citation statements)
references
References 30 publications
1
35
0
Order By: Relevance
“…To evaluate and possibly scale up our observed results to the landscape level for the Huachuca Mountains study area, we compared our observations on streamflow duration (as measured using ER sensors) to modeled data from Levick et al (2015) and Levick et al (2018). In brief, Levick et al (2018) simulated stream flow permanence using the AGWA/SWAT (Automated Geospatial Watershed Assessment Tool/Soil and Water Assessment Tool) for mapped streams in Fort Huachuca as a whole.…”
Section: Comparison Of Observed Streamflow and Water Presence To Modementioning
confidence: 99%
See 1 more Smart Citation
“…To evaluate and possibly scale up our observed results to the landscape level for the Huachuca Mountains study area, we compared our observations on streamflow duration (as measured using ER sensors) to modeled data from Levick et al (2015) and Levick et al (2018). In brief, Levick et al (2018) simulated stream flow permanence using the AGWA/SWAT (Automated Geospatial Watershed Assessment Tool/Soil and Water Assessment Tool) for mapped streams in Fort Huachuca as a whole.…”
Section: Comparison Of Observed Streamflow and Water Presence To Modementioning
confidence: 99%
“…To evaluate and possibly scale up our observed results to the landscape level for the Huachuca Mountains study area, we compared our observations on streamflow duration (as measured using ER sensors) to modeled data from Levick et al (2015) and Levick et al (2018). In brief, Levick et al (2018) simulated stream flow permanence using the AGWA/SWAT (Automated Geospatial Watershed Assessment Tool/Soil and Water Assessment Tool) for mapped streams in Fort Huachuca as a whole. Validation sites used by Levick et al (2018) were data from Gallo et al (2020), also reported in final report by Stromberg et al (2015), and these cluster validity data indicated that only five flow types existed on Fort Huachuca.…”
Section: Comparison Of Observed Streamflow and Water Presence To Modementioning
confidence: 99%
“…El‐Sadek, El Kahloun, and Meire (2008) and Ligdi, El Kahloun, and Meire (2010) argued that determining the eco‐hydrological status of a river basin permits integrated water resource management. Derivation of eco‐hydrological properties, that is, vegetation, hydrologic, and geomorphic attributes, can support management actions and improve decision‐making for ephemeral and intermittent streams (Levick et al, 2018). The principles of eco‐hydrology are useful in developing sustainable approaches aiming at managing river floodplain systems and minimizing the flood risk (Kiedrzyńska, Kiedrzyński, & Zalewski, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Advances in monitoring techniques and data analysis linked within an interdisciplinary interpretive framework aid in realizing and addressing the myriad of issues facing the dryland eco‐hydrological systems and effectively managing these systems (Wang et al, 2012). As indicated by Levick et al (2018), under the situation of large geographic extent of a study area and infeasible collection of intensive gauge‐based streamflow data, Geographic Information System (GIS)‐derived variables and hydrologic modelling can be alternatively utilized.…”
Section: Introductionmentioning
confidence: 99%
“…The recognition of the ubiquity of temporary streams and the concern over their vulnerability to climate change and other human disturbances have led to an increased number of studies on these systems in the last decades. The majority of these studies have focused on the ecological and biochemical functioning of temporary streams [8,10] and have highlighted their importance as: unique animal and plant habitats with high biodiversity [5,11]; migration corridors [12,13]; sources and sinks of organic matter and nutrients [4]; and biochemical hotspots with high reaction rates compared to neighboring environments [14].…”
Section: Introductionmentioning
confidence: 99%